Low-Lying Electronic States of the Nickel Dimer - Tamukong, Patrick K.; Hoffmann, Mark R. (Frontiers in Chemistry, 2021)
The generalized Van Vleck second order multireference perturbation theory (GVVPT2) method was used to investigate the low-lying electronic states of Ni2. Because the nickel atom has an excitation energy of only 0.025 eV to its first excited state (the least in the first row of transition elements), Ni2 has a particularly large number of low-lying states. Full potential energy curves (PECs) of more than a dozen low-lying electronic states of Ni2, resulting from the atomic combinations 3F4 + 3F4 and 3D3 + 3D3, were computed. In agreement with previous theoretical studies, we found the lowest lying states of Ni2 to correlate with the 3D3 + 3D3 dissociation limit, and the holes in the d-subshells were in the subspace of delta orbitals (i.e., the so-dubbed δδ-states). In particular, the ground state was determined as X 1Γg and had spectroscopic constants: bond length (Re) = 2.26 Å, harmonic frequency (ωe) = 276.0 cm-1, and binding energy (De) = 1.75 eV; whereas the 1 1Σg+ excited state (with spectroscopic constants: Re = 2.26 Å, ωe = 276.8 cm-1, and De = 1.75) of the 3D3 + 3D3 dissociation channel lay at only 16.4 cm-1 (0.002 eV) above the ground state at the equilibrium geometry. Inclusion of scalar relativistic effects through the spin-free exact two component (sf-X2C) method reduced the bond lengths of both of these two states to 2.20 Å, and increased their binding energies to 1.95 eV and harmonic frequencies to 296.0 cm-1 for X 1Γg and 297.0 cm-1 for 1 1Σg+. These values are in good agreement with experimental values of Re = 2.1545 ± 0.0004 Å, ωe = 280 ± 20 cm-1, and D0 = 2.042 ± 0.002 eV for the ground state. All states considered within the 3F4 + 3F4 dissociation channel proved to be energetically high-lying and van der Waals-like in nature. In contrast to most previous theoretical studies of Ni2, full PECs of all considered electronic states of the molecule were produced.